Pendelmobilität und Familiengründung : Zum Zusammenhang von berufsbedingtem Pendeln und dem Übergang zum ersten Kind - Skora, Thomas (Opladen : Verlag Barbara Budrich, 2018)
Studies show that assuming the role of parents - especially for women - is difficult to reconcile with long commutes. However, the directions of action are still unclear. Does starting a family reduce the willingness to commute longer and are professional disadvantages accepted for this? Or does commuting lead to the postponement of starting a family or even prevent it? With these research questions, the book sheds light on a new explanatory approach for lower employment opportunities in mothers and makes a contribution to the identification of determinants of fertility.
Print version record.
Keywords: Commuting; Working mothers; Married women -- Employment; Women employees; Labor mobility; Work and family; Work-life balance; Motherhood; Migrations alternantes; Mères au travail; Femmes mariées -- Travail; Personnel féminin.; Main-d'œuvre -- Mobilité.; Travail et familles; Conciliation travail-vie personnelle; Maternité.; maternity; SOCIAL SCIENCE / Sociology / Marriage & Family; Commuting; Labor mobility; Married women -- Employment; Motherhood; Women employees; Work and family; Work-life balance; Working mothers; Electronic books; Electronic books